Filostomide bats in zones with passive and active restoration of Could Forest - Serna-Lagunes, Ricardo; Miranda-Peralta, Julia Bibiana; Pérez-Lino, Jessica Dennise (Ecosistemas y Recursos Agropecuarios, 2024)
The Cloud Forest (CF) is a biodiverse ecosystem and key habitat for bats, but it is threatened by anthropogenic activities, with ecological restoration being a management strategy. The objective of the study was to compare the diversity of bats in an area with passive (ZRP) and active (ZRA) restoration of CF. During October 2019 to February 2020, three monitoring sessions were carried out with mist nets to capture bats, they were classified at the species level, trophic guild, risk category and tolerance to habitat modification; richness and abundance were estimated and compared using interpolation and extrapolation curves. With a capture effort of 4,860 m2 net/h and a sample coverage of 95% in the ZRP and 93% in the ZRA, 135 individuals of 13 species of the Phyllostomidae family were captured; of these, 90 individuals of 13 species were captured in the ZRA and 45 individuals of 8 species in the ZRP. The abundant species were Sturnira hondurensis with 48 (35.6%) and S. parvidens with 36 individuals (26.7%). Ten species were classified as frugivorous and three as hematophagous, and two species were classified as sensitive to habitat degradation. Dermanura watsoni and Diaemus youngui are subject to Special Protection. The ZRA conglomerated the highest abundance of bats, indicating that active restoration practices benefit frugivorous and reduce the presence of hematophagous species.